Nanostructuring of AlCu alloy NPs obtained by FLASiS† - Santillán, Jesica María José (2024)
In the nanometric scale, alloy nanomaterials behave as new materials since they are able to display structures and properties which are different from those of the pure metal nanostructures or bulk alloys. In this work, the compositional characteristics of AlCu alloy nanoparticles obtained by †Femtosecond Laser Ablation Synthesis in Solution (FLASiS) on solid targets with different percentages of Al and Cu were studied. Morphology, structure, composition and plasmonic behaviour of the nanoparticles were analysed by Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Energy-Dispersive X-ray Spectroscopy (EDS) and Optical Extinction Spectroscopy (OES). From the obtained results, underlying formation mechanism and a configuration model of a host alumina matrix with copper inclusions is proposed. Analysis of the plasmonic resonance spectral region in the extinction spectra of the synthesized colloids using this model show that the nanoparticles have a Cu filling factors of about 0.02 which agrees with those determined independently from TEM images. The amount of Al and Cu components in the nanoparticle depends on their relative percentages in the initial solid target. Here we describe the possible kinetic formation mechanism of these nanostructures.